Chromatography of alkaloids : Part A. Thin-layer chromatography - Baerheim-Svendsen, A.; Verpoorte, R.; ScienceDirect eBooks (Amsterdam : Elsevier Scientific Pub. Co., 1983)
The first of two books which provide an unparalleled reference source and handbook for everyone involved with alkaloid analyses. The first volume gives a comprehensive summary of the literature on thin layer chromatography of alkaloids. It presents the most effective methods for the separation and detection of alkaloids occurring in plant material, biological material, pharmaceutical preparations and drugs of abuse.
Adsorbents, solvent systems and TLC techniques -- Detection of alkaloids in TLC -- TLC separation and identification of alkaloids in general -- Isolation of alkaloids -- Pyrrolidine, pyrrolizidine, pyridine, piperidine and quinolizidine alkaloids -- Tobacco alkaloids -- Pseudotropine alkaloids -- Cinchona alkaloids -- Cactus alkaloids -- Isoquinoline alkaloids -- Opuim alkaloids -- Terpenoid indole alkaloids and simple indole alkaloids -- Ergot alkaloids -- Psilocybe alkaloids -- Steroidal alkaloids -- Xanthine derivatives -- Diterpene alkaloids -- Colchicine and related alkaloids -- Imidazole alkaloids -- Quarternary ammonium compounds.
Includes indexes.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Alkaloids -- Analysis; Chromatographic analysis; SCIENCE -- Chemistry -- Organic; Alkaloids -- Analysis; Chromatographic analysis; Electronic books